Hallucinations Relationship With The Level Of Family Conversation In Schizophrenia Patients - Fatmawati; Nurlina (Comprehensive Health Care, 2017)
According to the WHO (World Health Organization) in 2009 it is estimated that 450 million people worldwide are considering mental problems, around 10% of adults who have mental disorders now and 25% of the population are expected to increasingly need help each year. Mental disorders account for 13% of all illnesses and will grow to 25% by 2030, mental disorders are also related to self-defense, more than 90% of one million cases of personal protection each year due to mental disorders. The purpose of this research is to know the hallucinatory relationship with the level of family difficulties of schizophrenic patients in H. A. Sulthan Regional Hospital. Dg Radja Regency of Bulukumba. Anxiety is a problem that is characterized by feelings that will occur in something that will happen excessively. The study design uses non-experiment using cross-sectional. The population and sample in this study were all the families of schizophrenic patients who received hallucinations that took treatment patients who received 52 people in the mental clinic of RSUD. H. A. Sulthan Dg. Radja, a sample of 34 people were taken using a consecutive sampling technique using a questionnaire and observation sheet. Mann-Whitney U test results obtained p-value = 0.006 (p-value <0.05). Vision hallucinations were 12 people (33.3%), auditory hallucinations were 22 people (61.1%), while 18 were increased (52.9), mild were 11 people (32.4%), and weight was considered as many as 5 people (14.7%). The conclusions in this study indicate that there is a significant relationship between schizophrenia patient research at H. A. Sulthan Regional Hospital Dg. Bulukumba District Radja. Lent to families to increase knowledge about hallucinations and how to care to improve the family level.